School-to-Work Opportunities through the Lens of Youth Development. Education Reform and School-to-Work Transition Series - Zeldin, Shepherd; Charner, Ivan; Academy for Educational Development, Washington, DC. National Inst. for Work and Learning ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1996)
Although the school-to-work and youth development fields come from very different beginnings, they share the goal of preparing all young people, including "high-risk youth," for adulthood by learning in context, actively participating in their own learning, and being challenged and supported to excel. Despite their shared visions for youth, many school-to-work and youth development efforts have felt strong pressures to defend their own "turf." It is, however, possible to cite several cases of model school-to-work programs and strategies that have consciously or unconsciously employed a "youth development lens" in designing and implementing their programs. Those examples confirm that the school-to-work movement can benefit and be strengthened by incorporating a youth development perspective to serving young people and building bridges not only with schools and employers but also with the "youth development field," specifically national and community-based youth organizations. Youth development organizations can help school-to-work system developers consider the impacts of neighborhoods, families, and other broader environmental impacts on their programs. Furthermore, youth development organizations are well positioned to offer ongoing training and technical assistance to school-to-work providers and to bring a full range of community leaders, practitioners, and youths into school-to-work planning/implementation discussions. (Contains 22 references.) (MN)
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: RR91172012.
ERIC Note: For related documents, see ED 381 666-670, ED 384 815, and CE 070 986-987.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agency Cooperation; Education Work Relationship; Educational Needs; High Risk Students; High Schools; Outcomes of Education; Partnerships in Education; Student Development; Transitional Programs; Work Experience Programs; Youth Agencies; Youth Opportunities; Youth Programs; Youth Development Model; Reports, Research